Teacher Talk Analysis in The Youtube Video "Differentiated Learning on Self-Introduction" From SMAN 1 Pangkalan Susu Through FIAC - Feny Nursyahwa Aulia Tarigan; Rahmad Husein; Neni Afrida Sari Harahap (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study analyzes teacher talk in the YouTube video "Differentiated Learning on Self-Introduction" from SMAN 1 Pangkalan Susu using the Flanders Interaction Analysis Category (FIAC) system. Teacher talk, which includes both direct and indirect verbal interactions, plays a critical role in fostering an engaging and effective learning environment. The research focuses on identifying patterns of teacher-student interactions that support differentiated learning, a method designed to cater to individual student needs. The results reveal that indirect talk, such as accepting feelings and giving encouragement, accounts for 60.87% of the interactions, while direct talk, like giving instructions and lecturing, constitutes 39.13%. This balance suggests a strong emphasis on student engagement through supportive communication, essential for differentiated learning environments.